LINC00467 induces melanoma deterioration by targeting miR-485-5p/P21 Activated Kinase 1: Role of LINC00467 in melanoma - Ji, Zhoujing; Zhang, Jie; Zhang, Lili; Yang, Shengju; Li, Yangcheng; Gu, Lixiong (Journal of Medical Biochemistry, 2022)
Background: The purpose of the current research was to investigate the biological roles of LINC00467 in inducing melanoma deterioration.Methods: Differential level of LINC00467 in melanoma tissues and its prognostic value were analyzed in GEPIA, which were further confirmed in clinical samples we collected. Regulatory effects of LINC00467 on proliferation, migration and invasion capacities of A375 and SKMEL1 cell lines were examined by a series of functional experiments. Potential downstream targets of LINC00467 were identified through dual-luciferase reporter assay, and their synergistic role in melanoma process was finally explored by rescue experiments.Results: LINC00467 was up-regulated in melanoma samples, but it did not have a prognostic potential in melanoma. LINC00467 has the capacities to stimulate proliferation, migration and invasion of A375 and SKMEL1 cell lines. The feedback loop LINC00467/miR-485-5p/PAK1 was identified, which was responsible for inducing melanoma deterioration.  Conclusions: LINC00467 stimulates proliferation, migration and invasion capacities of melanoma via targeting miR-485-5p to upregulate PAK1, which provides potential targets for treatment of melanoma.
Keywords: Melanoma; LINC00467; MiR-485-5p; PAK1